The Development of Post-Modern Islamic Boarding Schools (Case Study at IHAQI Creative Pesantren in Bandung) - Nurti Budiyanti; Nurwadjah Ahmad; Andewi Suhartini; Muhamad Parhan (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
Religious education is fundamental to be improved, as moral degradation continues to take root around the world. One of the efforts to maintain the value of religious teachings is through the education system, among others through boarding school education. The presence of boarding schools in the middle of society is not only as an educational institution, but also as a religious and religious broadcasting institution. This research uses a qualitative approach with case study methods at IHAQI Boarding School Bandung Creative Boarding School. The results of the study illustrate that historically pesantren continues to change, in the 21st century pesantren developed using the word pondok to "Boarding School", one of them in IHAQI Creative Boarding School. This shows the birth of the modern post generation as a form of modern boarding school progress in the development of the industrial revolution 4.0 era, in addition to displaying religious knowledge, modern post pesantren that exists in the 21st century also displays various skills in various fields of science. Pesantren has a unique and creative Boarding School system in developing various disciplines and skills needed by the community. This pesantren became a post-modern boarding school that excelled in printing a generation of digital-based Islam. Its more comprehensive-holistic educational patterns make it more likely to create an ideal educational environment for giving birth to people who will be able to bring about a revolution in social, political, economic and religious life movements